Comparative study on the Body Physique and Physical Fitness Indexes of Chinese Male University Students and Pakistani Male International Students in China (International Journal of Physiotherapy, 2021)
Background: The body, physique and physical fitness of the university students of two countries would be different because their living environments are different. Therefore, this was arranged to assess the body shape, body function, and physical fitness of Chinese and Pakistani university students who study in China.Methods: Data was collected from (n = 30) Pakistani and (n = 30) Chinese students. The selected variables wereanthropometric measures, physical fitness, and physiological tests. Independent t-test and Pearson of correlation were applied for the statistical analysis.Results: results depict the Pakistani students were significantly superior to Chinese students in BMI (P < 0.00, shoulder length (P < 0.04), step test (P < 0.03), standing long jump (P < 0.00) and significantly inferior in sitting height (P >0.05), heart rate (P < 0.00), percentage of fat (P < 0.00), sit and reach (P < 0.00). There was significant correlation with waist circumference (P < 0.03), waist hip ratio (WHR) (P < 0.00), and negatively correlated to weight (P < 0.01), systolic blood pressure with diastolic blood pressure (P < 0.00). Bone mineral density was negatively correlated with heart rate(P < 0.03), and body fat (P < 0.01).Conclusion: the higher body size of Pakistani students is genetically affected, and the lesser in body composition and physical fitness is affected by their lack of physical activities. The study provides a layout of a chart to profile the physical status of Pakistani and Chinese university students.